2021
DOI: 10.1007/s40843-021-1838-3
|View full text |Cite
|
Sign up to set email alerts
|

Wide-range-adjusted threshold voltages for E-mode AlGaN/GaN HEMT with a p-SnO cap gate

Abstract: p-GaN cap layer has been recognized as a commercial technology to manufacture enhanced-mode (E-mode) AlGaN/GaN high electron mobility transistor (HEMT); however, the difficult activation of Mg doping and etching damage of p-GaN limit the further improvement of device performance. Thus, the more cost-effective cap layer has attracted wide attention in GaN-based HEMT. In this paper, p-type tin monoxide (p-SnO) was firstly investigated as a gate cap to realize E-mode AlGaN/GaN HEMT by both Silvaco simulation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Lukens et al reported a "first gate" selfaligning process using Mo as both the etched mask layer and the gate metal and found that the barrier degradation of the device did not occur after high-temperature annealing [45]. In view of the generally low breakdown voltage of p-GaN grid HEMTs, domestic and foreign researchers have continuously optimized and innovated the process or structure in recent years [46][47][48]. At present, the breakdown voltage is mainly improved by designing various field plate structures.…”
Section: P-gan Grid Technologymentioning
confidence: 99%
“…Lukens et al reported a "first gate" selfaligning process using Mo as both the etched mask layer and the gate metal and found that the barrier degradation of the device did not occur after high-temperature annealing [45]. In view of the generally low breakdown voltage of p-GaN grid HEMTs, domestic and foreign researchers have continuously optimized and innovated the process or structure in recent years [46][47][48]. At present, the breakdown voltage is mainly improved by designing various field plate structures.…”
Section: P-gan Grid Technologymentioning
confidence: 99%
“…With the excellent physicochemical properties, the wide bandgap semiconductor materials (such as SiC, GaN, AlGaN) are very suitable for high-temperature, high-frequency, and high-power semiconductor devices including diodes, detectors, and high-power electronic devices. [1][2][3] However, these devices are rarely able to go out of the laboratory and enter into industrialization because of the high cost of fabrication. Therefore, to reduce the cost of wide bandgap semiconductor devices is necessary for their practical application.…”
Section: Introductionmentioning
confidence: 99%